Multifocal Cryoballoon Ablation for Eradication of Barrett's Esophagus-Related Neoplasia: A Prospective Multicenter Clinical Trial - Canto, Marcia Irene; Trindade, Arvind J.; Abrams, Julian; Rosenblum, Michael; Dumot, John; Chak, Amitabh; Iyer, Prasad; Diehl, David; Khara, Harshit S.; Corbett, F. Scott; McKinley, Matthew; Shin, Eun Ji; et al. (The American journal of gastroenterology, 2020)
Ablation of Barrett's esophagus (BE) is the preferred approach for the treatment of neoplasia without visible lesions. Limited data on cryoballoon ablation (CBA) suggest its potential clinical utility. We evaluated the safety and efficacy of CBA in a multicenter study of patients with neoplastic BE. In a prospective clinical trial, 11 academic and community centers recruited consecutive patients with BE of 1-6 cm length and low-grade dysplasia, high-grade dysplasia (HGD), or intramucosal adenocarcinoma (ImCA) confirmed by central pathology. Patients with symptomatic pre-existing strictures or visible BE lesions had dilation or endoscopic mucosal resection (EMR), respectively, before enrollment. A nitrous oxide cryoballoon focal ablation system was used to treat all visible columnar mucosa in up to 5 sessions. Study end points included complete eradication of all dysplasia (CE-D) and intestinal metaplasia (CE-IM) at 1 year. One hundred twenty patients with BE with ImCA (20%), HGD (56%), or low-grade dysplasia (23%) were enrolled. In the intention-to-treat analysis, the CE-D and CE-IM rates were 76% and 72%, respectively. In the per-protocol analysis (94 patients), the CE-D and CE-IM rates were 97% and 91%, respectively. Postablation pain was mild and short lived. Fifteen subjects (12.5%) developed strictures requiring dilation. One patient (0.8%) with HGD progressed to ImCA, which was successfully treated with EMR. Another patient (0.8%) developed gastrointestinal bleeding associated with clopidogrel use. One patient (0.8%) had buried BE with HGD in 1 biopsy, not confirmed by subsequent EMR. In patients with neoplastic BE, CBA was safe and effective. Head-to-head comparisons between CBA and other ablation modalities are warranted (clinicaltrials.gov registration NCT02514525).